If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(-2) = r + 5r Multiply 6 * -2 -12 = r + 5r Combine like terms: r + 5r = 6r -12 = 6r Solving -12 = 6r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-6r' to each side of the equation. -12 + -6r = 6r + -6r Combine like terms: 6r + -6r = 0 -12 + -6r = 0 Add '12' to each side of the equation. -12 + 12 + -6r = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -6r = 0 + 12 -6r = 0 + 12 Combine like terms: 0 + 12 = 12 -6r = 12 Divide each side by '-6'. r = -2 Simplifying r = -2
| P(x)=(60x-0.3x^2)-(5x+13) | | 3x+1/3=3x-1/2 | | ln(16x)= | | 5x+14=2+7x | | -1(-1)=z | | 2cos(3x-1)=0 | | 32=2(x+4.5) | | (c^2-9c-5)-(-c^2-8c-10)= | | (x-4)2=(x-2)2 | | x^2-10*x+13=0 | | x^2-10*x+13= | | 7v-28=9+3v-1 | | (11b^2-7)+(15b^2-b)= | | (6y-8)+(5y-3)+(6y+4)=180 | | 50=.5*20V^2 | | -26.3+0.1p=0.9+5.3 | | 2y-5x=-8 | | x*x+4x+1=32 | | -12.1+0.5p=0.9+5.3 | | ln^5+ln(2x)=5 | | -[4(7)-(14(7)+8)]=8+(9(7)+7) | | 6+(-10)+(-2)+8= | | -12.1+.5=0.9p+5.3 | | -12+.5=0.9p+5.3 | | 3c+12=6c+11.31 | | 3c+12=6c+12.31 | | -5-2=1-2x+3x | | 2.3x+1.37=-11.74 | | -[4z-(14z+8)]=8+(9z+7) | | -91.9+n=-99 | | 0=-u+u | | -8(t-2)-(t+3)=10 |